PENDIDIKAN KARAKTER DALAM ISLAM Pemikiran Al-Ghazali tentang Pendidikan Karakter Anak Berbasis Akhlaq al-Karimah - Syamsul Kurniawan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2017)
It is the study on Al-Ghazali views of education about character education of children based moral character. According to the view, the character must be built since they were in early age. Hopefully, they know the difference between good and bad manners, and can determine their character (whether it is good or bad). The character education based moral character is aimed to form the positive character which leads to self-approach to God, in order to gain the happiness in the world and the hereafter.